Pengembangan Aplikasi Perangkat Bergerak Penjemputan Sedekah Barang Bekas di Kota Malang Berbasis Geolokasi dan Algoritme Nearest Neighbor (Studi Kasus: Yayasan Rumah Singgah Mualaf Malang) - Cahyono Hadi Kurniawan; Lutfi Fanani; Muhammad Aminul Akbar (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2020)
Zakat, infaq and alms is one of the important instruments in the life of the Muslim community. Because with those, the poor can be empowered and have easy access to capital to do business. The hope of the amil zakat institution to improve the procedures for collecting zakat, infaq, and alms is getting bigger so that it can provide better accommodation for muzakki to give alms, invest, and give alms to be distributed to the less fortunate. But in an era of technological advancement like now, the collection of zakat, infaq and alms in Malang is not as expected. A common example that still does not use technology is the Malang Mualaf Home Shelter Foundation. Every week there are 5 - 7 muzakki that take advantage of the alms collection feature. However, the collection of used goods alms at the Mualaf Malang Home Selter Foundation still only uses contact persons from the committee so that the collectors are less efficient. Along with technological developments and times, many closest route search algorithms have developed, one of which is the nearest neighbor algorithm. By utilizing geolocation data that is converted into distance units and the nearest neighbor algorithm, the alms collection committee gets a more efficient alms pickup route compared to manual technology which is currently still in use.